An application of CFD to improve warm-up performance of the 3-way auto-catalyst by high surface area and low thermal mass. (20th February 2004) - Jeong, Soo-Jin; Kim, Woo-Seung; Kim, Taehun
Mathematical modelling of three-way catalytic converter (3WCC) operation is used increasingly in the optimisation of automobile converter systems. But almost all of previous computational models were based on an "adiabatic one-channel" approach with the reaction kinetics computations, which is useful and efficient in predicting real-world performance of the catalyst. However, as long as flow maldistribution is not accounted for in the models, simulation results will not be reliable. In this work, 2-dimensional performance prediction of catalyst has been performed by using turbulent flow simulation coupled with reaction mechanism for surface chemistry and the results were compared with experimental data and one channel simulation in the literature. The computational results from this study show the better prediction accuracy in terms of CO, HC and NO conversion efficiencies compared to those of the 1-D adiabatic model. Varying cell density and hot spot moving pattern within the monolith during warm-up period are also considered. The results indicate that the higher cell density giving much larger geometric surface area shows the faster movement of thermal front of hot spot due to the higher convective heat transfer rate.